Effect of blue, green or red LED light on the functional quality of spinach (Spinacia oleracea L.) - Battistoni, Benjamín; Amorós, Asunción; Tapia, María Luisa; Escalona, Víctor Hugo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2021)
The present study employed white (W), blue (B: 468 nm), red (R: 629 nm) and green (G: 524 nm) monochromatic LED lights for 26 days, from 11:00 to 18:00 (7 h per day), with a average of photosynthetic photon flux density (PPFD) of 26.00 m-2 s-1 on two baby leaves of spinach (Spinacia oleracea L.) cultivars (Falcon F1 and Viroflay) grown in a hydroponic system. Regardless of the cultivar, the fresh and dry weights were positively influenced when the plants were irradiated by R-light in comparison to W-light. Independent of the cultivar, the leaves treated with B-light reached a significantly higher phenolic compound concentration than plants irradiated with W-light. With respect to antioxidant capacity, plants treated with B-light showed a significantly higher antioxidant capacity than those treated with W-light. According to the results, the use of LED lights is a promising technique for the production of antioxidant compound-enriched vegetables. Highlights - The fresh and dry weights were positively influenced when baby leaves spinach were irradiated by red LED light. - Baby leaves spinach treated with blue LED light reached a significantly higher phenolic compound concentration and antioxidant capacity. - The green LED light increased total phenolic compound concentration in baby leaves spinach.